The aims and circumstances of the form and spirit: AbdulHamid AbuSulayman’s engagement with the hadith and sunnah - Bin Jamil, Khairil Husaini (2023)
This paper reviews the methodology of AbdulHamid AbuSulayman in dealing with the hadith and the sunnah of the Prophet Muhammad PBUH. It is undeniably recognised that in his grand vision of reform and the practical projects he inspired during his lifetime, the scholar has dealt with numerous issues pertaining to the recognition, the understanding, and the implementation of the sunnah of the Prophet. Several of his writings forwarded some significant ideas in the interpretation of the sunnah. Having been associated with the school of Islamisation of knowledge, AbdulHamid contributed to the construct of the methodology and the principles in dealing with hadith and sunnah adopted by the proponents of the agenda. The present paper attempted to study AbdulHamid’s methodology in the subject particularly his attention to debates on the form and the spirit of the sunnah. This is done through several methods: (1) a thorough analysis of the available literature and writings produced by the scholar, (2) an interview with scholars of hadith who were working in the International Islamic University Malaysia during the scholar’s rectorship, and (3) a brief analysis of secondary works that provided responses to his ideas and messages. The research will also examine AbdulHamid’s methodology in dealing with the hadith and the sunnah, incorporating seven themes: 1) the form and conception, 2) the function and authority, 3) the technical verification, 4) the interpretation, 5) the application and implementation, 6) the preservation and sustentation, and 7) the encounter with philosophical discourse. By carrying out some comparisons and critical assessments, the paper hopes to provide a comprehensive understanding of AbdulHamid’s endeavour with regard to the Sunnah and its role in the civilisational reform of the Muslim world.